IMPLEMENTASI KEBIJAKAN BANTUAN SOSIAL TUNAI DI KELURAHAN TALIKURAN UTARA KECAMATAN KAWANGKOAN UTARA MINAHASA - Supit, Brain Fransisco; Lumingkewas, Elvis (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aimed to 1) analyze how the Cash Social Assistance program implementation, and 2) to know the Social Cash Assistance program impact to community. Qualitative research method was used in this study with purposive sampling. The research located in the North Talikuran Village Administration, North Kawangkoan Sub-District, Minahasa Regency. The study results show that 1) Cash Social Assistance fund distribution to participants in Talikuran Utara is right on target. 2) The Cash Social Assistance Program has impacts, both positive and negative, to communities. This fund can really help beneficiary communities in their daily lives (Positive impact), while the negative impact is that this program creates a culture of reliance and sluggishness.